2022
DOI: 10.1186/s12917-022-03346-w
|View full text |Cite
|
Sign up to set email alerts
|

3T Magnetic resonance imaging and computed tomography of the bovine carpus

Abstract: Background Lameness in cattle is a major health problem and causes great economic losses. Carpal injury is a common cause of forelimb lameness in cattle. Radiography and/or ultrasonography of the carpus is a challenge due to complex anatomy of the joint. Additional imaging using computed tomography (CT) or magnetic resonance imaging (MRI) may be indispensable for reaching a decisive diagnosis. Precise evaluation of the clinical CT and MRI images necessitates an in-depth knowledge of the normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…The obtained results are in agreement with previous reports in horses and cattle con rming that MRI offers the best evaluation technique for all anatomical structures in the carpal joint, particularly the soft tissue structures [5,8,15]. The MRI sequences used in this study were selected as they were successfully used for assessment of the carpal region in equine, bovine and canine [15][16][17]. The MRI settings were re ective of the parameters used in equine orthopedic MRI and the acquisition durations for the used sequences were satisfactory if used in clinical patients [18].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The obtained results are in agreement with previous reports in horses and cattle con rming that MRI offers the best evaluation technique for all anatomical structures in the carpal joint, particularly the soft tissue structures [5,8,15]. The MRI sequences used in this study were selected as they were successfully used for assessment of the carpal region in equine, bovine and canine [15][16][17]. The MRI settings were re ective of the parameters used in equine orthopedic MRI and the acquisition durations for the used sequences were satisfactory if used in clinical patients [18].…”
Section: Discussionsupporting
confidence: 92%
“…It permitted a distinctive depiction of articular cartilage, cortical and subchondral bone as well as the ligamentous and tendinous structures, which is not completely possible by other diagnostic modalities. The obtained results are in agreement with previous reports in horses and cattle con rming that MRI offers the best evaluation technique for all anatomical structures in the carpal joint, particularly the soft tissue structures [5,8,15]. The MRI sequences used in this study were selected as they were successfully used for assessment of the carpal region in equine, bovine and canine [15][16][17].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our data revealed that there is no distal sesamoid bones in examined camels; the phalanges and sesamoid bones of the forelimb were alike to those in the hind limb; this finding was agreed upon (Al‐Redah & Hussin, 2016; Smuts & Bezuidenhout, 1987). While in the cattle, the proximal and distal sesamoid bones are observed in the one‐humped camel ( Camelus dromedarius ) (El‐Shafey & Kassab, 2013; Nahas et al., 2024) and buffalo ( Bos bubalis ) (El‐Shafey & Kassab, 2013). Of these, two, the third and fourth metacarpal bones, were fully developed and had three phalanges; four proximal sesamoids were present, two for each digit; and two distal sesamoids were also present, one for each digit, while the second and fifth small metacarpal bones are vestiges and are placed behind the fetlock; each contains one or two small bones that do not articulate with the rest of the skeleton (Getty, 1975).…”
Section: Discussionmentioning
confidence: 99%